Urgensi Pengamalan Kembali Kaidah Isnad dalam Meminimalisir Penyebaran Hoaks: Studi Kasus Maraknya Penyebaran Hoaks oleh Kalangan Intelektual Dosen - Zahrotus Saidah (Indonesian Journal of Islamic Education Studies (IJIES), 2019)
Spreading hoax is increasingly difficult to dammed. This phenomenon not only found in people with a low literacy level but also in intellectual circles whose literacy levels are considered high, such as lecturers. Then, become urgent to immediately formulate an effective effort to minimize the increasingly widespread of hoax. One effort that has been taken by an Islamic Institution in Cirebon is by study and practice the implied message of the principles of the validity of the hadith trough the Hadith Study Course. This study aimed to identify the factors that caused the lecturers to ignore isnad and to find out the impact of contextual learning on the rules of hadith in terms of understanding and application. This is qualitative research. The main sources of data are interviews with lecturers, indirect observations, questionnaires, and FGD with students. The supporting sources include books, articles, and news related. The results of this study are: 1) the factors that caused lecturers to leave isnad is due to the lack of inspiration and practice of the norms, 2) the application learning hadits with the contextual approach is more effective in helping students understanding and practice the rules of isnad and matan in their daily activity